Real-World Outcomes in Patients with Branch Retinal Vein Occlusion- (BRVO-) Related Macular Edema Treated with Anti-VEGF Injections Alone versus Anti-VEGF Injections Combined with Focal Laser. (20th May 2021) - Thomley, Meredith E.; Gross, Cole N.; Preda-Naumescu, Ana; Chen, Kelly S.; Swain, Thomas; Mason III, John O.; Crosson, Jason N.
Abstract : The purpose of this study was to assess outcomes in a real-world nonclinical trial setting of antivascular endothelial growth factor (VEGF) injections alone vs. focal laser combined with anti-VEGF injections in patients with branch retinal vein occlusion- (BRVO-) related macular edema (ME). This study included 88 BRVO with ME patients who were treated over three years at both a tertiary referral center in the Birmingham metropolitan area and satellites in rural Alabama. One group received only anti-VEGF injections ( n  = 56); the other group received both anti-VEGF injections and focal laser ( n  = 32). The following outcome measures were evaluated: initial and final visual acuities (VA), initial central subfield thickness (CST) on OCT, number of injections, number of lasers, percentage of patients with a gain of 3 lines of VA, percentage of patients with VA better than or equal to 20/40, and percentage of patients with VA worse than or equal to 20/200. We found that there was no difference in initial VA (p = 0.913 ) or CST (p = 0.961 ) between the two groups. The injection only group required a median of 7 injections, while the combination group required a median of 4 injections, but this was not a statistically significant difference (p = 0.117 ). There was no difference in final VA (p = 0.414 ) or any of the other visual outcomes between the two groups. In conclusion, focal laser did not decrease the number of injections required or improve the VA in BRVO-related ME. Although visual outcomes were similar in both groups, focal laser does not appear to be of additional benefit in BRVO-related ME in the anti-VEGF era.